SUN-506 Hyperthyroidism Induced Hepatic Apoptosis - Ahmed, Sabreen (J Endocr Soc, 2020)
Background: Graves’ disease is commonly associated with abnormal liver function tests, most frequently ALP, but the exact mechanism is not fully understood. In vitro and in vivo animal studies have shown elevated T3 activity can induce hepatocyte apoptosis via a mitochondrial-mediated pathway. This case demonstrates a patient with elevated aminotransferases and hepatic apoptosis most likely secondary to severe hyperthyroidism. Clinical Case: 50 year old female with a past medical history of migraines was seen by primary care for fatigue and 15 lb weight loss in one month. She was found to be hyperthyroid with TSH < 0.1 uIU/L (n=0.34-5.6), free T4 3.48 ng/dL (n=0.58-1.64) and mildly elevated aminotransferases of AST 77 IU/L (n=15-41), ALT 144 IU/L (n=12-63), which increased within a week to 159 IU/L and 309 IU/L respectively. ALP and bilirubin were within normal range. She was started on methimazole 20 mg twice daily by her PCP. The patient developed vomiting and stopped taking methimazole after 3-4 days. Upon initial presentation to endocrine clinic, found to be clinically hyperthyroid and as LFTs were improved but still elevated, she was re-challenged with methimazole at a lower dose as well as started on a beta blocker and cholestyramine. TT3 checked was elevated at 2.10 ng/mL (n 0.87-1.78). Graves’ disease was confirmed with elevated TSI as well as RAI uptake and scan showing increased homogenous uptake. She had extensive workup for another etiology by hepatology including autoimmune, which were negative. Her fibrosis score was stage F1-F2 (n=F0) and necroinflammatory activity grade A3 indicating severe activity (n=grade A0). Core needle biopsy of the liver showed focal lytic necrosis/apoptosis and abundant pigment-laden Kupffer cells signifying recent hepatocellular injury. Her AST and ALT down trended and normalized with repeat fibrosis score of F1 and necroinflammatory activity grade A0. She eventually had definitive therapy with RAI treatment. Conclusion: In most cases of hyperthyroid induced liver dysfunction, liver histology showed fatty infiltration, cytoplasmic vacuolization, nuclear irregularity and hyperchromatism. This case, without any other known causes that could explain her hepatic injury, indicates the possible role of hyperthyroidism in hepatic apoptosis.